2013
DOI: 10.1109/tmi.2013.2280903
|View full text |Cite
|
Sign up to set email alerts
|

Improved Shear Wave Motion Detection Using Pulse-Inversion Harmonic Imaging With a Phased Array Transducer

Abstract: Ultrasound tissue harmonic imaging is widely used to improve ultrasound B-mode imaging quality thanks to its effectiveness in suppressing imaging artifacts associated with ultrasound reverberation, phase aberration, and clutter noise. In ultrasound shear wave elastography (SWE), because the shear wave motion signal is extracted from the ultrasound signal, these noise sources can significantly deteriorate the shear wave motion tracking process and consequently result in noisy and biased shear wave motion detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 41 publications
5
70
0
Order By: Relevance
“…Figures 5 and 6 show the comparison results between the pediatric P7-4 Fundamental-TAST shear wave detection sequence and the P7-4 PIHI-TAST shear wave detection sequence, using identical shear wave push beams. Corroborating prior in vivo adult transthoracic scans [1], harmonic imaging shear wave detection demonstrated substantial improvement of shear wave signal quality as compared to fundamental imaging. Although a higherfrequency fundamental frequency (5 MHz) was used for shear wave detection, the ultrasound signal was severely contaminated by the strong clutter noise (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures 5 and 6 show the comparison results between the pediatric P7-4 Fundamental-TAST shear wave detection sequence and the P7-4 PIHI-TAST shear wave detection sequence, using identical shear wave push beams. Corroborating prior in vivo adult transthoracic scans [1], harmonic imaging shear wave detection demonstrated substantial improvement of shear wave signal quality as compared to fundamental imaging. Although a higherfrequency fundamental frequency (5 MHz) was used for shear wave detection, the ultrasound signal was severely contaminated by the strong clutter noise (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized that chemo-induced cardiotoxicity may change the passive stiffness of the myocardium, which can be noninvasively and quantitatively measured by ultrasound SWE. Previous studies have shown the feasibility of transthoracically measuring diastolic myocardial stiffness for adults [1,2]. To date, pediatric implementation of cardiac SWE has not been established and its feasibility has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to appreciate these events a temporal resolution of close to 2 ms would be necessary [1]. In the last decade propagating events have been noted in vivo using different US modalities such as Tissue Doppler Imaging (TDI) and B-mode [2][3][4][5][6][7][8][9][10]. These studies all use velocity curves to describe the electromechanical coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated a substantial improvement of shear wave motion detection using pulse-inversion harmonic imaging (PIHI) [5]. Ultrasound harmonic signals are less vulnerable to clutter noises caused by reverberations from subcutaneous tissues [6], and have a finer resolution cell which favors accurate shear wave motion calculation [7].…”
Section: Introductionmentioning
confidence: 99%